امام رازی و آمدی کے فقہی نظریات کا تقابلی مطالعہ : منتخب پہلووں میں تفردات و اشتراکات: A Comparative Study of the Jurisprudential Theories of Imam Razi and Al-Amidi: Unique Aspects and Commonalities in Selected Areas - Hafiz Muhammad Hanif; Hafiz Ahmad Mahmood; Qari Hafiz Ullah Khan (International Research Journal of Arabic and Islamic Studies, 2022)
This study provides a comparative analysis of the jurisprudential theories of Imam Razi and Al-Amidi, focusing on selected aspects of their legal thought. It examines the distinctive features (tafarrudat) and commonalities (ishtirakat) in their approaches to Islamic jurisprudence. The research highlights the unique contributions of each scholar and identifies the areas where their legal theories converge. By exploring their methodologies and interpretations, the study aims to shed light on the diverse perspectives within Islamic legal scholarship and the nuanced differences that characterize their juristic approaches.